2015
DOI: 10.1016/j.expneurol.2014.08.006
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and sex differences in the brain: A genome-wide comparison of histone-3 lysine-4 trimethylation (H3K4me3) in male and female mice

Abstract: Many neurological and psychiatric disorders exhibit gender disparities, and sex differences in the brain likely explain some of these effects. Recent work in rodents points to a role for epigenetics in the development or maintenance of neural sex differences, although genome-wide studies have so far been lacking. Here we review the existing literature on epigenetics and brain sexual differentiation and present preliminary analyses on the genome-wide distribution of histone-3 lysine-4 trimethylation in a sexual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
62
0
1

Year Published

2016
2016
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(66 citation statements)
references
References 87 publications
3
62
0
1
Order By: Relevance
“…75%) had greater H3K4me3 in females, and this was seen whether the sex chromosomes or autosomes were considered ( figure 5). Also, as in [50], sex differences in H3K4me3 did not map closely onto gene expression [52]. Genes with greater H3K4me3 in females were significantly associated with synapse structure and function; the expression of such genes is presumably tightly regulated in both sexes, but males and females may do it differently.…”
Section: Whole-genome Studies Of Sex Differences In Epigenetic Mechanmentioning
confidence: 97%
See 2 more Smart Citations
“…75%) had greater H3K4me3 in females, and this was seen whether the sex chromosomes or autosomes were considered ( figure 5). Also, as in [50], sex differences in H3K4me3 did not map closely onto gene expression [52]. Genes with greater H3K4me3 in females were significantly associated with synapse structure and function; the expression of such genes is presumably tightly regulated in both sexes, but males and females may do it differently.…”
Section: Whole-genome Studies Of Sex Differences In Epigenetic Mechanmentioning
confidence: 97%
“…The distribution of genes with differential H3K4me3 in the BNST/ POA of adult mice showed a sex bias; most of the genes had more of this histone mark in females than in males (red and pink shading). This was true for both autosomal and X-chromosome genes [52]. (Online version in colour.…”
Section: Whole-genome Studies Of Sex Differences In Epigenetic Mechanmentioning
confidence: 99%
See 1 more Smart Citation
“…Chromatin immunoprecipitation followed by deep sequencing (ChIP-Seq) has been used in different cell types of primate brain (human and non-human) to examine the genome-wide distribution of H3K4me3 (Cheung et al 2010). However, surprisingly there are very few studies exploring sex-specific regulation of mono-, di and tri-methyl H3K4 (H3K4me1/H3K4me2/H3K4me3) marks on a genome-wide scale (Shen et al 2015). This is particularly intriguing, given that several studies have reported subtle sex-dependent differences in the expression of H3K4- demethylase and methyltransferase enzymes for various brain regions.…”
Section: Histone Modificationsmentioning
confidence: 99%
“…Secondly, the use of marijuana by women could possibly impact not only their immediate health, but also the health of their offspring, and such potential long-term consequences are still not known. It is clear that the biological differences between males and females influence the development of neuropsychiatric phenotypes (Figueira and Ouakinin, 2010; Savic and Engel, 2014; Shen et al, 2015), but the ways in which marijuana use causes long-term problems that affect the two sexes remain largely unexplored. As such, the inclusion of females in studies of cannabis is essential to decipher the neurobiological systems vulnerable in the different sexes to also ultimately guide targeted treatments in a sex-specific manner.…”
Section: Introductionmentioning
confidence: 99%